Hi, I was solving an integral and got this substitution

t= tg(x/2) then sin(x) = (2t)/(1+t^2) and cos(x) = (1-t^2)/(1+t^2)

How did I get sin(x) = (2t)/(1+t^2)?

I know that t = sinx/(cosx+1) and sinx = [(cosx+1)*t]

Results 1 to 4 of 4

- Jun 18th 2013, 12:27 PM #1

- Joined
- May 2013
- From
- Uruguay
- Posts
- 4
- Thanks
- 1

- Jun 18th 2013, 01:54 PM #2

- Joined
- Apr 2005
- Posts
- 18,948
- Thanks
- 2737

- Jun 18th 2013, 03:53 PM #3

- Joined
- Jun 2009
- Posts
- 671
- Thanks
- 136

- Jun 27th 2013, 11:42 AM #4

- Joined
- May 2013
- From
- Uruguay
- Posts
- 4
- Thanks
- 1